An uphill struggle : current issues in UK defence acquisition - Smith, Jeremy C. D.; Antill, Peter D. (Cranfield University, 2013)
Both the Strategic Defence and Security Review (SDSR) 2010 and Lord Levene’s ‘Defence Reform’ report of 2011 have again drawn attention to the variable performance of the Ministry of Defence (MoD) in acquisition matters and highlighted a number of underlying reasons along with a series of recommendations on how it could address them. Such a situation, where the MoD has to conduct a major transformation while managing a vast portfolio of activity, has been made all the more critical by the impact of the financial crisis and economic recession. To help reduce the UK’s budgetary deficit, defence is expected to deliver savings estimated at £4.3 billion by 2014-2015. This article looks at the current issues that are facing the UK MoD during this time of transition in respect of defence acquisition.